Effects of volumetric ice content and strain rate on shear strength under triaxial conditions for frozen soil samples - Arenson, Lukas U.; Johansen, Martha M.; Springman, Sarah M. (Permafrost and Periglacial Processes, 2004)
ISSN:1045-6740 ISSN:1099-1530